Estimating the contribution of occupational solar ultraviolet exposure to skin cancer3. (January 2014) - Milon, A.; Bulliard, J.‐L.; Vuilleumier, L.; Danuser, B.; Vernez, D.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Solar radiation is the most frequent occupational carcinogenic agent in many countries. It is also the main causative factor of skin cancer. Skin cancer is barely recognized as an occupational disease due to a lack of data on the occupational contribution to the overall dose. What does this study add? We show the contribution of occupational ultraviolet exposure, in terms of annual (chronic) anatomical dose and acute events, to the risk of squamous cell carcinoma (SCC) for various occupational scenarios. A numerical model (SimUVEx) was used to assess occupational and lunch break exposure, and to characterize exposure patterns and anatomical distribution. Risk of SCC was estimated from an existing epidemiological model.